(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
The study of African personal names has interested a number of researchers from diverse fields. Focus on Christian beliefs in the postcolonial period and on the linguistic forms and the meanings communicated through these forms provides revealing insights to the relationship between language use and its sociocultural context, itself the concern of anthroponomastics. Zimbabwe’s political independence in 1980 represented a more robust Christian tradition and provided a framework for linguistic freedom that resulted in dynamic and creative ways of expressing Christian faith. Naming assumed exciting dimensions. The present study reveals the revitalisation of the traditional culture where naming is a specific, conscious and deliberate linguistic act intimately linked with values, traditions, hopes, fears and events in people’s lives. The data discussed in this article shows how black Zimbabwean parents communicate messages reflecting these dispositions through names that they create for their children in insightful, inventive and systematic ways in the postcolonial period.